Speech development after cochlear implantation in infants with isolated large vestibular aqueduct syndrome. (2nd November 2019) - Li, Yang; Kong, Ying; Xu, Tianqiu; Dong, Ruijuan; Lv, Jing; Qi, Beier; Wang, Shuo; Yan, Fei; Li, Yongxin; Long, Mo; Chen, Xueqing
Abstract: Background: Few studies on speech performance of children after cochlear implantation (CI) described isolated large vestibular aqueduct syndrome (LVAS). Objective: To investigate speech developmental trajectories of infants with LVAS after CI, and to compare with those who have structurally normal inner ears. Materials and methods: 1112 infants with congenital severe to profound hearing loss participated in this study. 150 infants in group A were diagnosed with LVAS, 962 infants in group B with structurally normal inner ear. The speech performance was assessed via the Meaningful Use of Speech Scale (MUSS). The evaluations were performed pre-implant, 1, 3, 6, 9, 12, 24, 36, 48 and 60 months after CI. Results: The mean scores of the MUSS improved over a 5-year period after implantation in both groups A and B. The LVAS group presented similar speech developmental trajectory to the non-LVAS group at each assessment interval, except pre-operation. There were significant differences in mean scores between vocalizing behavior and oral communication skills, clarification skills of infants in both two groups. Conclusions and significance: Speech performance of infants with LVAS developed rapidly after CI and was similar to infants with structurally normal inner ear. For infants with isolated LVAS, CI had a significant effect and should be recommended as a therapeutic option.